Magnetic properties of nanostructrured (Co/Cu/Co)/Fe/Si multi-layer - (:unkn) unknown (ELSEVIER SCIENCE BV, 2008)
Magnetic multi-layer (Cu/Co)(60)/Fe film on Si(001) substrate have been investigated. The magnetic parameters such as saturation magnetization, coercive field, and magnetic anisotropies have been determined from ferromagnetic resonance (FMR) and DC magnetization data. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: ferromagnetic resonance; magnetic multi-layer; MAGNETORESISTANCE